INFLUENCE OF HUMAN RESOURCE MANAGEMENT PRACTICES ON EMPLOYEES’ PRODUCTIVITY, DEPARTMENT OF NATIONAL REGISTRATION BUREAU, NAIROBI COUNTY - KYENZI, EUNICE KALUKI (Machakos University Press, 2022)
The purpose of this study was to determine the influence human resource practices on the employees’ productivity, department of National Registration Bureau Nairobi County.National Registration Bureau (NRB) department is one of the key departments in the Ministry of Interior and Coordination of National Government in the Office of the President. It operates under the State Department of Interior. The specific objectives of the study were: to establish the influence of performance appraisal on employees’ productivity in the National Registration Bureau Department in Nairobi County, to determine the influence of training on productivity of employees in the National Registration Bureau Department in Nairobi County, to establish the influence of compensation on employees’ productivity in the National Registration Bureau Department in Nairobi County. The study adopted the following theories: Expectancy theory, Goal setting theory and Human capital theory. The study used descriptive research survey design to collect primary data from the respondents, using closed and opened ended questionnaires. The study had a target population of eight hundred (800) officers comprising of top level officers, middle level managers and technical officers and support staff. It employed stratified and systematic random sampling. The data collected was analyzed quantitatively by use of descriptive statistics e.g. frequencies and percentages and it used Statistical Package for Social Sciences (SPSS) alongside inferential statistics and qualitatively by use of content analysis. The findings were that the Staff Training in National Registration Bureau Department helps in improving the morale of employees as well as giving them job security and job satisfaction hence increase productivity. Training also improves efficiency and productivity of employees. Well trained employees show both quantity and quality performance. On Performance appraisal in the NRB department the study found that it provides an opportunity to recognise and reward employees and to ensure they feel valued for the work that they do. Finally the study found out that the right compensation and benefits schemes ensure that hard-working employees are rewarded fairly and in the most cost-effective way for the company. This in turn then motivates employees to sustain their performance. The study recommends that training should be the teaching, or developing in oneself or others, any skills and knowledge that relate to specific useful competencies. It should have specific goals of improving one's capability, capacity, productivity and performance. Performance appraisal should be done frequently to help keep everyone well updated of his or her performance. Compensation should create an appropriate reward system for workers and employers and should reflect the value of a job. Now that the study was undertaken in Nairobi County further research can be undertaken in other counties to establish if the findings of this study are same in other counties.